Development of a new and efficient synthesis method of 1,2,4-triazole-5- thione derivatives [1,2,4-Triazol-5-Tiyon türevi bileşiklerin elde edilmesi için yeni ve etkili bir sentez yöntemi geliştirilmesi] - (:unkn) unknown (My University, 2013)
3,4-Disubstituted-2,4-dihydro-5H-1,2,4-triazole-5-thiones were synthesized by a new one-pot, two-step synthesis method which was demonstrated to be superior than the current synthesis methods. The new method involves addition of alkyl/aryl isothiocyanates to substituted hydrazides in ethanol following the refluxing process of intermeadiate in 4N sodium hydroxide solution. According to our new synthesis procedure, reaction has gone to completion within 6 hours by higher product yields and reduced solvent usage.
Keywords: 1,2,4-triazole-5-thione; Method development; Synthesis